Periodontal parameters in prediabetes, type 2 diabetes mellitus, and non-diabetic patients - Mohammed ALASQAH; Sameer MOKEEM; Ali ALRAHLAH; Nawwaf AL-HAMOUDI; Tariq ABDULJABBAR; Zohaib AKRAM; Fahim VOHRA; Fawad JAVED (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of the present study was to compare the clinical and radiographic periodontal parameters in prediabetes, type 2 diabetes mellitus (T2DM), and non-diabetic patients. Forty-one patients with prediabetes (Group 1), 43 patients with T2DM (Group 2), and 41 controls (Group 3) were included. Demographic data were recorded using a questionnaire. Full-mouth clinical (plaque index [PI], bleeding on probing [BOP], probing depth [PD], clinical attachment loss [CAL], missing teeth [MT]) and radiographic (marginal bone loss [MBL]) parameters were measured on digital radiographs. In all groups, hemoglobin A1c (HbA1c) levels were also measured. P values less than 0.05 were considered statistically significant. The mean age and HbA1c levels of participants in Groups 1, 2, and 3 were 53.4±3.5, 60.1 ± 0.6, and 56.6 ± 2.5 years and 6.1%, 8.4%, and 4.8%, respectively. The mean duration of prediabetes and T2DM in patients from Groups 1 and 2 were 1.9 ± 0.3 and 3.1 ± 0.5 years, respectively. PI, BOP, PD, MT, CAL, and MBL were significantly higher in Groups 1 (p < 0.05) and 2 (p < 0.05) than in Group 3. There was no statistically significant difference in these parameters in Groups 1 and 2. Periodontal parameters were worse between prediabetes and T2DM patients compared with controls; however, these parameters were comparable between prediabetes and T2DM patients.